Effect of Level of Protein on Digestibility and Nitrogen Balance in Sudan Desert Sheep Fed Molasses-Based Fattening Rations - Lutfi, Asim A. A.; Fadl, Soad A. (University of Khartoum Journal of Agricultural Sciences, 2023)
Three yearling intact males of Sudan desert sheep (Hamari ecotype) ranging in weight between 26 and 30 kg were used in a 3x3 latin square design with the objective of studying the effect of feeding three crude protein (CP) levels (14.5%, 16.7% and 18.7%) in complete iso- caloric molasses-based diets on nitrogen-balance, digestibility of nutrients, rectal temperature and respiration rate. Nitrogen (N) level had no significant effect on the digestibility coefficients of the different nutrients, total digestible nutrients (TDN) and N-balance. Urine volume, rectal temperature and respiration rate were not affected by N level.